PERLINDUNGAN HUKUM KONSUMEN ATAS PEMBATALAN TIKET PESAWAT - Diana Mora Jambak; Nabilla Zaskia Putri; Lilawati Ginting (KOLONI, 2022)
Issues regarding compensation for flight cancellations during a pandemic must be resolved is a concern of the government as a policy maker and airlines as a responsible party according to laws and international conventions concerning air transportation, one of which is the Aviation Law and the Consumer Protection Law. Covid-19 are causing problems regarding the form of cash compensation which was replaced with a voucher and the return procedure which was considered to be many times longer and even threatened that no compensation would be given. Therefore, the author analyzes to find out the factors that cause these problems and how airline responsibility and consumer protection should be in terms of laws and regulations. In addition, there was a significant spike at one time in requests for cancellation and the following Government Regulation No. 25 of 2020, which abolished the cash refund policy, turned out to be one of the factors in the increasing number of consumer complaints about compensation issues and has clearly contrary to the laws and regulations.